Designing an AI-Based Village Information System Using Research and Development Approach for Public Governance Modernization in Popalia Village - Arafat, Arafat; Rasyid, Rasmiati; Hestiana, Sry; Rendi, Rendi; Bantun, Suharsono; Sari, Jayanti Yusmah (Jurnal Teknik Informatika (Jutif), 2025)
The COVID-19 pandemic has highlighted the challenges faced by village administrations in managing public services that remain highly manual, inefficient, and prone to errors. This study aims to design an Artificial Intelligence (AI)-based Village Information System to improve administrative efficiency, accuracy, and accessibility. The research employs a Research and Development (R&D) approach through requirement analysis, system design, prototype development, integration of an AI Generative Model and a Natural Language Processing (NLP) chatbot, followed by functional testing using the Black-box method and usability evaluation with the System Usability Scale (SUS). The results show that functional testing achieved a 95% pass rate and the SUS evaluation scored 87.0, placing the system in the “Excellent” category. These findings indicate that the system effectively automates document creation, validates citizen data, and supports interactive services through an NLP-based chatbot. The study contributes to the modernization of digital village governance in Indonesia by demonstrating how AI integration can reduce administrative workload, minimize errors, and enhance service quality.